Green’s Function for a Slice of the Korányi Ball in the Heisenberg Group Hn - Shivani Dubey; Ajay Kumar; Mukund Madhav Mishra (International Journal of Mathematics and Mathematical Sciences)
We give a representation formula for solution of the inhomogeneous Dirichlet problem on the upper half Korányi ball and for the slice of the Korányi ball in the Heisenberg group Hn by obtaining explicit expressions of Green-like kernel when the given data has certain radial symmetry.